Aproximación a un plan de negocio para la comercialización y exportación de panela pulverizada a Roma - Italia (2020)
Traditional Colombian products are being affected by low retail prices, which is why most traditional productions are ending unleashing the technological non-development and stagnation of the sector, which is why it is vital to start doing Emphasize first of all the product, making a difference, that is, obtaining a food with added value that is desired and that stands out against what has been produced long ago. The search for an internationalization of the product achieves that again the activation of the market and the production of panela increase considerably, where a large number of peasant families are benefited in addition to being in the sights of the government that provides different aid through different entities with You look to the economic progress of the country.